Math, asked by yashj9902, 2 months ago

+ (2x²-3x + 5) (3x+3x-5)​

Answers

Answered by IlphysicslI
20

\tt\large{""" ❤️ Answer ❤️ """}

simplify, we will proceed as follows:

(2x2+3x−5)(3x2−5x+4)

=2x2(3x2−5x+4)+3x(3x2−5x+4)

(Distributive law)

=6x4−10x3+8x2+9x3−15x2+12x−

=6x4−10x3+9x3+8x2−15x2−15x2

(Rearranging)

=6x4−x3−22x2+36x−20

(Combining like terms)

Thus, the answer is

6x4−x3−22x2+36x−20

.

Answered by nibedita50
1

Step-by-step explanation:

pls mark me as BRAINLIEST.

Attachments:
Similar questions